Frontispiece: Reversal of a Single Base‐Pair Step Controls Guanine Photo‐Oxidation by an Intercalating Ruthenium(II) Dipyridophenazine Complex. Issue 29 (13th July 2015) - Keane, Páraic M.; Poynton, Fergus E.; Hall, James P.; Sazanovich, Igor V.; Towrie, Michael; Gunnlaugsson, Thorfinnur; Quinn, Susan J.; Cardin, Christine J.; Kelly, John M.
<x xml:space="preserve">Abstract</x> DNA Photooxidation Small changes in DNA sequence can have major biological effects. P. M. Keane, C. J. Cardin, J. M. Kelly et al. show on page 8364 ff. that the reversal of a single base‐pair step has a dramatic effect on the guanine photooxidation by a DNA‐intercalating RuII complex.